Effect of land rehabilitation measures on soil organic carbon fractions in semi-arid environment - Mutio, James Mumo; Kebeney, Syphyline; Njoroge, Ruth; Churu, Harrison; Ng'etich, Wilson; Mugaa, Denis; Alkamoi, Boniface; Wamalwa, Fred (Frontiers in Sustainable Food Systems, 2023)
Soil erosion threatens the sustainable intensification of food systems among smallholder farmers in arid and semi-arid lands (ASALs). Intensifying adoption of soil mitigation and rehabilitation measures is thus needed urgently in these ASALs, but scaling up these measures depends on scientific evidence of their contributions to key components of sustainable intensification such as soil organic carbon. However, there is no information on how existing mitigation and rehabilitation measures influence soil carbon fractions and carbon management indices in ASALs. This study evaluated the influence of soil erosion mitigation and rehabilitation measures on soil carbon fractions and management indices in Arenic Lixisols of semi-arid environments in West Pokot County, Kenya. We evaluated different vegetation types (maize-beans intercrop and pastures) with and without two locally developed terrace designs for soil conservation (Fanya Juu and Fanya Chini). Combining terracing with annual cropping significantly increased total organic carbon (TOC). The highest TOC (13 g C kg−1) was recorded in pasturelands with terraces while degraded land with no intervention was found to have the lowest TOC (6.0 g C kg−1). Terraced farms with longer residence time (>4 years old) had significantly higher organic carbon than (<4 years old). Other soil properties remained stable with terrace age (1–5 years). Labile SOC and non-labile SOC differed significantly within and across vegetation types with or without terraces (p < 0.05). Pasture and crop systems with terraces had high labile SOC content of 5.9 g C kg−1 and 7.2 g C kg−1, respectively. Labile SOC followed the TOC trend with terrace age, i.e., increasing from 1 year to 5 years old. Combined pasture and terraces had a significantly higher carbon management index (CMI) of 161.7, or 14 times the CMI found in degraded systems with no interventions and 1.5 times the combined crop system with terraces. CMI was also directly correlated with residence time terraces had stayed in the crop system, increasing from 1 year to 5 years old. Contrary to CMI and other indices, the weighted enrichment ratio was found to inversely correlate with age of terrace. Improvement of carbon content and CMI resulted from restorative measures and likely improved soil quality and ecosystem functions. Although terraces play a significant role in the restoration of degraded soils as indicated by the above-mentioned changes, they are most beneficial when used in combination with croplands because of the high level of disturbance and flows of both inputs and outputs of carbon for these croplands.